Emergence and evolution of an entrepreneurial ecosystem: the case of Porto - Corbo, Leonardo (2019)
Current work on entrepreneurial ecosystems is still underdeveloped, focusing prevalently on successful case studies such as Silicon Valley and less on peripheral areas where entrepreneurship is a nascent but growing phenomenon. In this paper, we examine the emergence and evolution of the entrepreneurial ecosystem of Porto, a city located in the north of Portugal, which has historically been an industrial hub but has witnessed a proliferation of start-ups in recent years. We find that for an entrepreneurial ecosystem to emerge it is of critical importance that one or more players assume the role of entrepreneurial hubs, even if in the initial stage interaction between these actors is limited. However, for an entrepreneurial ecosystem to grow additional factors are necessary including a wide range of experienced investors and a strong level of interaction within the ecosystem. We discuss the implications of our findings for research on entrepreneurial ecosystems and outline a possible avenue for future inquiry.